Penggunaan Media Roda Pintar untuk Meningkatkan Kemampuan Membaca Permulaan Kelas I Sekolah Dasar - Azka Salmaa Salsabilah; Ika Nur Muzamil; Indri Fitriani Juardi; Nabila Putri Nur Afifah; Rachel Fadila Putri Herdiansyah; Prihantini Prihantini (Journal on Education, 2024)
Reading is a complex and complicated process to master in practice. Lack of comprehension skills in beginning reading is caused by factors that come from within the student and factors from outside the student. One alternative that can be used in learning beginning reading is smart wheel media. This research uses a qualitative approach with a literature study method. The purpose of this study was to examine the use of smart wheel media as an alternative in improving the beginning reading skills of grade I elementary school students. Through the use of Smart Wheel media, it can be effective in helping grade I elementary students develop beginning reading skills. With a creative, interactive approach, and involving all students, the use of this media can create a pleasant learning atmosphere and support the development of reading skills in the early stages of learning.